The development of a professional capabilities framework for social work in Aotearoa New Zealand. - Ballantyne N; Beddoe L; Hay K; Maidment J; Walker S; Merriman C (Aotearoa New Zealand Association of Social Workers, 2022)
Introduction: This research brief discusses methods used to co-produce a professional capabilities framework as the final part of a larger programme of research on enhancing the professional capabilities of newly qualified social workers. Methods: This phase of the research programme began with a literature scan of five social work professional capability frameworks then used this information, along with data from earlier parts of the study, to engage a range of key stakeholders in co-production workshops using a structured, participatory, World Café approach. Findings: Analysis of the data from the co-production workshops identified seven core values that underpinned capable social work practice in Aotearoa. It also identified ten core capabilities with a clear professional practice focus that were strongly supported by workshop participants. Implications: Professional capabilities frameworks can guide and inform learning experiences of social workers at all levels of practice. The data collected during this phase of the project informed further development of the ten capabilities using a staged approach to practice development at three levels.